2019
DOI: 10.20944/preprints201909.0033.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Major Depression in Children with β-Thalassemia Major is Strongly Associated with the Number of Blood Transfusions, Iron Overload and Increased Levels of Interleukin-1β

Abstract: Beta-thalassemia major (β-TM) patients are treated with repeated blood transfusions, which may cause iron overload (IO), which in turn may induce immune aberrations. Patients with β-TM have an increased risk of major depressive disorder (MDD). The aims of the present study are to examine whether repeated blood transfusions, IO and immune-inflammatory responses are associated with MDD in children (6-12 years) with β-TM. The Children’s Depression Inventory (CDI), iron status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In Arab communities, in 2012, a study reported similar findings from 80 patients in Lebanon where 35% of patients were depressed [ 19 ]. In the study by Al-Hakeim et al, it was reported that major depression in children with BTM was strongly associated with the number of blood transfusions, iron overload, and increased levels of interleukin-1ß [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Arab communities, in 2012, a study reported similar findings from 80 patients in Lebanon where 35% of patients were depressed [ 19 ]. In the study by Al-Hakeim et al, it was reported that major depression in children with BTM was strongly associated with the number of blood transfusions, iron overload, and increased levels of interleukin-1ß [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression, anxiety, and stress (DAS) are psychological disorders, which can complicate BTM patients' condition and cause multiple comorbidities if they were not diagnosed early and managed appropriately [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current therapies for β-TM include blood transfusion yielding almost normal life expectations 4,5 . Since the human body has no regulated mechanism to excrete excess iron, secondary iron overload occurs rapidly in patients, who are on chronic blood transfusion programs.…”
Section: Introductionmentioning
confidence: 99%